Recycled granulates manufacturing from spent refractory wastes and magnesium based binder. (15th February 2023) - Seco, A.; del Castillo, J.M.; Perlot, C.; Marcelino, S.; Espuelas, S.
Highlights: Magnesia refractories are able for granulates manufacturing. Mg based binders showed hydration, hydroxylation and carbonation processes. CO2 curing modified the granules bulk density. CO2 curing did not modify the granules water absorption. CO2 curing increased the granules mechanical properties. Abstract: This paper analyzes the ability of two Spent Refractory Wastes (SRW) for the manufacturing of recycled granulates for construction applications. A binary magnesium oxide and ground granulated blast furnace slag hydraulic binder was considered as an agglomerating agent for the granulates manufacturing. Influence of curing atmosphere was carried out: in air, 20 % CO2 and 100 % CO2 atmosphere up to 28 days. Granulometry, thermal analysis, particle density, bulk density, water absorption and mechanical strength tests were performed to characterize the granulates. SRW showed their ability for the granulates manufacturing. Results demonstrated the existence of a residual reactivity of the wastes considered. A direct relationship between the CO2 content of the curing atmosphere and the granulates hydration degree was observed. Carbonation process increased from 7 days to 28 days and direct relationships were observed between the CO2 content and the carbonation degree as well as between the binder dosage and the carbonation degree. CO2 curing reduced the water absorption and increased the compressive strength of the granulates.